ABA enhances the apoptotic effect of docetaxel in the multidrug-resistant DU145 prostate cancer cell line - Şumnulu Deniz; Doğanlar Zeynep Banu (Archives of Biological Sciences)
This study aimed to induce drug resistance in DU145 prostate cancer cells by exposing them to docetaxel and mitoxantrone, and to examine the effects of combining docetaxel and abscisic acid (ABA). The IC50 values for docetaxel and mitoxantrone in non-resistant cells were 54.57 nM and 6.25 nM, respectively, rising to 808.53 nM and 50.07 nM after resistance had developed. RT-PCR analysis showed that treatment of resistant cells with 50.07 nM docetaxel and 500 μM ABA (ABA) resulted in the following changes in gene expression: heat shock protein (HSP) 70 (0.63-fold), glucose-regulated protein 94 (GRP94) 0.33-fold, inositol-requiring transmembrane kinase endoribonuclease-1α (IRE1α) 1.62-fold, ER degradation- enhancing alpha-mannosidase-like 1 (EDEM1) 1.77-fold, X-box binding protein 1 (XBP1) 1.53-fold, p21 (2.53-fold), cellular tumor antigen p53 (p53) 2.49-fold, bcl-2-like protein 4 (Bax) 2.7-fold, and tumor necrosis factor (TNF-α) 6.35-fold. Tali™ cytometry analysis showed a 47% increase in apoptotic/necrotic cells with the combined treatment of docetaxel and ABA, compared to a 26% increase with docetaxel alone. Fluorescent staining revealed that co-administration of docetaxel and ABA increases apoptosis in resistant DU145 cells compared to treatment with docetaxel alone. This study suggests that combining ABA with docetaxel could be effective in drug-resistant prostate cancer.